1981
DOI: 10.1007/bf01959904
|View full text |Cite
|
Sign up to set email alerts
|

Insulin effect in vitro on human erythrocyte plasma membrane

Abstract: The effect of porcine insulin has been tested in vitro on human erythrocyte plasma membrane (Na+-K+) and Mg2+-ATPase activities as well as on membrane fluidity. The results indicate that the hormonal treatment significantly inhibits (Na+-K+)-ATPase activity, and at the same time decreases membrane fluidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
2
6
1
Order By: Relevance
“…The ghosts were frozen before use, and we observed virtually the same results with fresh and frozen thawed erythrocyte ghosts. Furthermore, the fluorescence polarization values from our control frozen ghosts (P =0.255_+0.037) were in a good agreement with those previously published using fresh erythrocytes by Beguinot et al [19] and by Luly et al [20]. We observed that erythrocyte membranes obtained from uncontrolled Type 1 diabetic patients had a decreased fluorescence polarization value compared to normal when using DPH as a probe.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The ghosts were frozen before use, and we observed virtually the same results with fresh and frozen thawed erythrocyte ghosts. Furthermore, the fluorescence polarization values from our control frozen ghosts (P =0.255_+0.037) were in a good agreement with those previously published using fresh erythrocytes by Beguinot et al [19] and by Luly et al [20]. We observed that erythrocyte membranes obtained from uncontrolled Type 1 diabetic patients had a decreased fluorescence polarization value compared to normal when using DPH as a probe.…”
Section: Discussionsupporting
confidence: 81%
“…Luly et al [20] were able to show an elevation of the fluorescence polarization value of normal erythrocyte membrane when incubated with physiological concentration of insulin. Dutta-Roy et al [27] showed that the microviscosity of normal erythrocyte membrane and the filtration time of intact cells were reduced by insulin at physiological concentration in a dose-dependent manner; use of supraphysiological concentration of the hormone reversed the effect of the lower concentration of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to the results obtained for erythrocyte membranes from healthy subjects by Luly et al [15], who found increased rigidity of erythrocyte membranes treated with insulin. However, our results corroborate those of Bailey et al [16], who observed a similar fluidity increase of rat adipocyte plasma membrane with insulin treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Mg 2+ -ATPase (EC 3.6.1.3.) also closely binds to the membrane; its activity is lower after incubation of erythrocytes with linoleic acid (15) but shows no sensitivity to insulin treatment (5) or membrane fluidity (10), in contrast to Na + -K + -ATPase.…”
mentioning
confidence: 98%
“…To act on membrane or intracellular proteins (3), the insulin receptor is believed to trigger various processes through individual or coordinated routes (4). The effect of insulin or receptor (insulin bound) on membrane-bound enzymes has been reported extensively (5)(6)(7)(8), and direct action of the hormone on isolated plasma membranes of liver (9) and erythrocyte (5) has been demonstrated. In erythrocytes the in vitro hormone-receptor interaction could affect membrane fluidity (5), resulting in an alteration of the membrane microenvironment responsible for variations in activity of membrane-bound enzymes [e.g., Na + -K + -ATPase (EC 3.6.1.4.…”
mentioning
confidence: 99%